If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(n + -5) = 48 Reorder the terms: 8(-5 + n) = 48 (-5 * 8 + n * 8) = 48 (-40 + 8n) = 48 Solving -40 + 8n = 48 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + 8n = 48 + 40 Combine like terms: -40 + 40 = 0 0 + 8n = 48 + 40 8n = 48 + 40 Combine like terms: 48 + 40 = 88 8n = 88 Divide each side by '8'. n = 11 Simplifying n = 11
| 2y+24=4y-6 | | 36=2(x-5) | | 2Y(0.5x)=x-4 | | 12+4n=24+6n | | Z=-8i | | 3x-15+x=5 | | 0.2x^2-0.4x-1=1-3x | | 10-6y=12-8y | | 5y=x^2-2x-5 | | 4x+5=-21-5x | | 3.2p+4=2p-2 | | 3.2+4=2p-2 | | 6x-1=5(x+1) | | 14x+y=3*14 | | 2x+3-4=8x+3 | | y=(4sinx)(8cosx) | | 24/(4/3) | | 5*ln(2a-1)=15 | | x^4-6x^3+4x^2-24x=0 | | 3x^2-13(x-y)+4=0 | | (2/7)x=42 | | 3x^2y^2-13x-13y+4=0 | | 2x(x+1)=5-2x | | .05x+.1y=1 | | 0=3x^2-18-48 | | 9n+11=65 | | 2y+18+5y= | | 5x+10=8x | | 3x^4-4x^3+3=0 | | 7secx+7tanx=7 | | 5n-3+2n+6=3n+4-7n-9 | | 3(2x-6)=6(2x+1) |